2008
DOI: 10.1111/j.1745-7254.2008.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor and cancer, buddies or foes?

Abstract: Tumor necrosis factor (TNF) is a multifunctional cytokine that plays important roles in diverse cellular events such as cell survival, proliferation, differentiation, and death. As a pro-inflammatory cytokine, TNF is secreted by inflammatory cells, which may be involved in inflammation-associated carcinogenesis. TNF exerts its biological functions through activating distinct signaling pathways such as nuclear factor-κB (NF-κB) and c-Jun N-terminal kinase (JNK). NF-κB is a major cell survival signal that is ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
394
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 574 publications
(435 citation statements)
references
References 155 publications
6
394
0
10
Order By: Relevance
“…[35][36][37] Furthermore, VEGF expression was found to be markedly increased and correlated with microvessel density in nasopharyngeal carcinoma patients. 30 Similarly, we herein found that TNFAIP2 is a downstream target of TNFa that acts as a potential angiogenic factor, as shown by the association of its expression with microvessel density in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…[35][36][37] Furthermore, VEGF expression was found to be markedly increased and correlated with microvessel density in nasopharyngeal carcinoma patients. 30 Similarly, we herein found that TNFAIP2 is a downstream target of TNFa that acts as a potential angiogenic factor, as shown by the association of its expression with microvessel density in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…High doses of human recombinant TNF-α were found to exert a powerful anti-cancer effect by inducing cell apoptosis and inhibiting tumor blood vessel formation. However, in low doses and with chronic stimulation, TNF-α could induce angiogenesis, proliferation, invasion and metastasis of tumor cells [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Tumor necrosis factor alpha (TNFα), a pleiotropic cytokine, mediates a broad range of proinflammatory activities, cell proliferation, differentiation and death (12,13). After stimulation with TNFα, three pathways can be initiated (14 -16).…”
Section: Introductionmentioning
confidence: 99%